2014
DOI: 10.1007/s10681-014-1212-3
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genome size changes (variation) in synthetic tetraploids of daylily (Hemerocallis) in relation to their diploid counterparts

Abstract: Tetraploids of daylily have taken a leading position among the daylily cultivars due to desirable traits such as vigorous growth and flowers with more intense colour. In our previous studies, several tetraploids of daylily cultivars 'Blink of an Eye' and 'Berlin Multi' were obtained using in vitro techniques with different antimitotic agents (colchicine, oryzalin, trifluralin, and amiprophos methyl). The purposes of this study were to evaluate changes in daylily tetraploids in relation to their diploid counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 53 publications
2
20
0
Order By: Relevance
“…Polyploids (usually tetraploids) are most often obtained in vitro or ex vitro by treatment with an antimitotic agent, and plants of desirable ploidy are selected using FCM. This approach was successfully performed for 3 Hibiscus species, Rhododendron hybrid R. × kosterianum, Syringa vulgaris × S. pinnatifolia, a few Rosa species, Gerbera jamesonii, Hemerocallis × hybrida, and Petunia axillaris (Rose et al, 2000;Väinölä, 2000;Van Huylenbroeck et al, 2000;Allum et al, 2007;Crespel et al, 2015;Podwyszyńska et al, 2015;Regalado et al, 2017). The induction of artificial polyploidy can also increase the production of important medicinal compounds and for this reason was introduced into Ocimum basilicum, Thymus persicus, and Trachyspermum ammi (Omidbaigi et al, 2010;Tavan et al, 2015;Noori et al, 2017).…”
Section: Plant Breedingmentioning
confidence: 99%
“…Polyploids (usually tetraploids) are most often obtained in vitro or ex vitro by treatment with an antimitotic agent, and plants of desirable ploidy are selected using FCM. This approach was successfully performed for 3 Hibiscus species, Rhododendron hybrid R. × kosterianum, Syringa vulgaris × S. pinnatifolia, a few Rosa species, Gerbera jamesonii, Hemerocallis × hybrida, and Petunia axillaris (Rose et al, 2000;Väinölä, 2000;Van Huylenbroeck et al, 2000;Allum et al, 2007;Crespel et al, 2015;Podwyszyńska et al, 2015;Regalado et al, 2017). The induction of artificial polyploidy can also increase the production of important medicinal compounds and for this reason was introduced into Ocimum basilicum, Thymus persicus, and Trachyspermum ammi (Omidbaigi et al, 2010;Tavan et al, 2015;Noori et al, 2017).…”
Section: Plant Breedingmentioning
confidence: 99%
“…In turn, 'Jonathan 2-4-4' had significantly thicker lamina and a higher chlorophyll content than diploid ' Jonathan'. These phenotype characteristics of chimeric cultivars indicate their tetraploidy in L2 since tetraploids of apple (Lespinasse and Noiton, 1986;Blanke et al, 1994;Sedysheva and Gorbacheva, 2013) and many other species (Jaskani et al, 2005;Elradi and Unal, 2010;González-Rodríguez and Grajal-Martín, 2013;Podwyszyńska et al, 2015) have larger and thicker leaves and often a higher chlorophyll content. Our supposition corresponds well with the reports on Hemerocallis ploidy chimeras 2-4-4 and 2-4-2 whose stomata were the same size as in diploids but the leaf sizes were as in tetraploids (Arisumi, 1964;Podwyszyńska et al, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…In general, polyploidy is associated with enhanced nuclear DNA content that translates into larger nuclei, cells and stomata sizes. It is often related to variation in morphological, physiological or phenological characteristics such as, e.g., larger leaves, flowers and fruits or late flowering time (Webster, 1996;Jaskani and Khan, 2000;Ramanna and Jacobsen, 2003;Anssour et al, 2009;Rogalska et al, 2007;Podwyszyńska et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ploidy-dependent gene regulation has been studied in plants under abiotic and biotic stresses [38,39]. Previous results revealed that tetraploid Paulownia was superior to its corresponding diploid as it had better timber quality, higher activity of peroxidases and superoxide dismutase, larger stoma size, and higher stress resistance [15,16], and changes in gene expression between diploid and tetraploid Paulownia have been reported [17,28,40,41], but these results were based on de novo transcriptome data, which might not provide sufficient evidence to fully understand ploidy-dependent gene regulation.…”
Section: Discussionmentioning
confidence: 99%